Dialog Incognito Tentang Penderitaan Mesias Dalam Perjalanan Menuju Emaus - Nggebu, Sostenis (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Christ's suffering and tribulation are an important aspect of the Christian faith, yet there are still many believers who do not understand it biblically This is reflected in the narrative of the journey of two disciples of Jesus to Emmaus, where they were confused about the meaning of the Messiah's suffering on the way to Emmaus. This article aims to explain the relevance of Christ's suffering and tribulation that can be an inspiration to the church, showing that the call to be a follower of Christ is inseparable from the possibility of facing suffering. Christians are called to remain steadfast in the faith and also to bear active witness to Christ's work in the world, even in these difficult situations. The method used in this study is theological study. The results of the study show that the doubts of the two disciples of Jesus were resolved when Jesus appeared in their midst and explained His identity and mission as the Messiah who must suffer for the salvation of mankind. That Christ's suffering was not for His own sake, but for the redemption of sinners, that they might be reconciled to the eternal God.